FEATURES OF SPATIAL DISTRIBUTIO OF P- AND S-WAVE VELOCITIES AND ELASTIC CHARACTERISTICS OF THE CRUST OF THE EASTERN CRIMEAN PENINSULA - Gobarenko V.S. (My University, 2001)
Some special characteristics of the deep structure and anomalies of the elastic properties of the crust of Eastern Crimea were established. The area studied was subdivided into three blocks, which were essentially different with regard to their velocities and elastic parameters. The crust between Alushta and Sudak is characterised by high values of all elastic parameters. It is assumed that elastic energy is accumulated in and discharged at the most contrasting inhomogeneities in the transition zone to the Sudak-Feodosia area of low velocity.